Class against class: the Communist Party of Great Britain in the third period, 1927-1932 - Worley, Matthew (1998)
This thesis provides an analysis of communism in Britain between 1927 and 1932. In these years, the Communist Party of Great Britain (CPGB) embarked upon a 'new period' of political struggle around the concept of class against class. The increasingly draconian measures of the Labour Party and trade union bureaucracy between 1924 and 1927 significantly restricted the scope of communist influence within the mainstream labour movement. As such, the CPGB - in accordance with the Communist International - attempted to establish an 'independent leadership' of the working class.